Death Attitudes and Death Anxiety Among Medical Interns After the 2020 Outbreak of the Novel Coronavirus - He, Yiqing; Li, Tao (Frontiers in Psychology, 2022)
This study investigates the status quo and influencing factors of death attitudes and death anxiety among medical interns in China as measured by the Death Attitude Scale and Death Anxiety Scale following the outbreak of "Novel Coronavirus Pneumonia" in China in early 2020. Results of this study show that under the influence of COVID-19, in terms of death attitude, medical interns scored the highest in neutral acceptance and the lowest in escape acceptance. There were significant differences in death attitude and anxiety among the groups with different backgrounds, including their families’ approaches to discussions of death, the number of funeral experiences, and other factors. There were two additional factors affecting attitudes that were related to the epidemic situation: whether the individual had participated in work to treat COVID-19 and whether their close friends or relatives (“cherished persons”) had been diagnosed with COVID-19. The study reveals the ways that the epidemic had an impact on death attitude and death anxiety.